Comparative study of serum electrolytes Na+, K+, Ca++ in patients of chronic kidney disease in relation to its severity - Behera, Bibhu P. (International Journal of Research in Medical Sciences, 2020)
Background: Chronic kidney disease (CKD) is a worldwide public health problem. Globally, CKD is the 12th cause of death and the 17th cause of disability, respectively. Yearly incidence of ESRD in India is approximately 150-200 pmp. Methods: The observational study was conducted in Department of General Medicine, Pandit Raghunath Murmu Medical College Hospital, Baripada between May 2018 and January 2019. 244 patients of Chronic Kidney Disease above 15 years of age satisfying the inclusion and exclusion criteria were included in the study. Results: Study group constitutes 64.34% (157) of male and 35.66% (87) of female patients with M:F of 1.8:1. The average age of the patients in the study was 55.91±12.49 yrs. 42.21% (103) of the patients were between 46 and 60 years of age. Maximum number of cases (190 cases) (77.87%) are in stage 4 and 5 with e-GFR <30 ml/ min. The average serum electrolytes in this study group for serum sodium, potassium, calcium are 137.31±10.05 mEq/L, 4.12±1.48 mEq/L and 1.10±0.19 mmol/L respectively. When association of hypokalemia with risk factor (known and unknown) is compared, chi-square value found to be 13.664 (p=0.0002) which is statistically extremely significant. Conclusions: Authors found significant number of cases, more commonly younger patients, presented with atypical manifestations having no specific etiology; the cause may be defect in rennin-angiotensin system or, may be genetic or, may be environmental.